Drought response of cowpea (Vigna unguiculata (L.) Walp.) landraces at leaf physiological and metabolite profile levels - Gomes, Ana M.F. (2021)
Drought threatens the world’s food production, particularly in Sub Saharan Africa low external input and rain fed agricultural systems, where cowpea (Vigna unguiculata (L.) Walp.) is an important food crop. In the context of growing concerns regarding climate changes implications on water availability, this study aimed at 1) to evaluate the drought responses in cowpea landraces with contrasting drought tolerance levels (A55 – high sensitivity; A80 - mild sensitivity; A116 - tolerant), 2) using an integrated physiological (leaf gas exchanges; chlorophyll a fluorescence) and biochemical (photoprotective pigments; RuBisCO activity; primary metabolite profiling) analysis to identify drought tolerance probes, in plants submitted to three water availability levels (well-watered, WW; mild drought, MD; severe drought, SD). A116 plants maintained a better water status under drought, what could justify the higher Pn and Pnmax values in MD, as well as higher photochemical use of energy (reflected in the photochemical quenching (qL) and in the quantum yield of non-cyclic electron transport (Y(II))), and the lower need of photoprotective thermal dissipation mechanisms (given by the non-photochemical quenching (qN), and the quantum yield of regulated energy dissipation at photosystem PSII (Y(NPQ))), in MD and SD plants. Greater declines of net (Pn) and potential (Pnmax) photosynthesis were observed in A55 plants, which frequently showed significant impacts already under MD conditions in most parameters, whereas A80 usually displayed and intermediate behaviour. Still, even A55 showed some acclimation response, regarding photoprotective mechanisms associated with high contents of zeaxanthin, lutein, and carotenes, and high Y(NPQ), and qN values, supporting the absence of an increase in the non-regulated energy dissipation at PSII (Y(NO) did not increased) even in SD plants. Additionally, A55 was not significantly affected in RuBisCO activity, which showed to be quite resilient in cowpea. A primary metabolite profiling, complemented with a partial least square discrimination analysis (PLS-DA), allowed a better separation of A116 and A55 plants according to their degree of drought tolerance. In response to drought, A116 showed the greatest accumulation of most responsive metabolites, 14 in total, with sucrose, fucose, urea, alanine and putrescine being exclusively increased in this genotype, suggesting that they can be candidates as drought tolerance proxies. Other compounds, as proline, valine, isoleucine (among amino acids), and rhamnose and raffinose (among sugars) showed close increase patterns